KAJIAN YII FRAMEWORK DALAM PENGEMBANGAN WEBSITE PERGURUAN TINGGI - Ary Budi Warsito; Muhamad Yusup; Yulianto Yulianto (Universitas Raharja, 2014)
Along with the development of technology in building a website , usually in the PHP programming language , people tend to write the coding from scratch . It seems like Perguruan Tinggi Raharja website which has 4 ( four ) such problems in terms of appearance , contains , security and technology . Because the Perguruan Tinggi Raharja website is still under construction using conventional methods , which take a long time can eventually lead to problems such as complexity in the preparation of the program code . Where it can lead to the development of the website and the length of time it is difficult to perform more maintenance because the code of the compiled program does not have a good standard of application development . As a solution presented four (4 ) solution of the above problems is the infrastructure including a website , view websites , website content and dashboard system , this can be managed more easily by applying a PHP based frameworks like Yii Framework . Yii Framework is a framework that contains functions and classes using the MVC method contained therein . MVC is a method that separates the parts of a web application consists of a Model , View , and Controller . With the Yii Framework significant benefits obtained as easily perform all types of web application development because Yii is very light and comes with a caching solution that is satisfactory , and it is suitable for developing applications with high traffic . In terms of safety also has a pretty good level of security , including the prevention of cross- site scripting ( XSS ) , cross-site request forgery , and the prevention of attacks of cookies . With the construction of university websites using Yii Framework Prog expected to improve the performance of a website as a future spotlight Pribadi Raharja information .